Management and outcomes of coronary artery perforations treated with the block and deliver technique. Issue 2 (28th August 2020) - Sanz Sanchez, Jorge; Garbo, Roberto; Gagnor, Andrea; Oreglia, Jacopo; Mazzarotto, Pietro; Maurina, Matteo; Regazzoli, Damiano; Gasparini, Gabriele L.
A bstract: Objectives and Background: Coronary artery perforation (CAP) is a potentially life‐threatening complication during percutaneous coronary interventions (PCI) and the best strategy for its management is yet to be proved. We aimed to analyze the safety, efficacy, and long‐term clinical outcomes of the block and deliver (BAD) technique, as only anecdotal cases are reported in literature. Methods: From January 2016 to January 2020, all consecutive patients treated with the BAD technique at five high‐volume centers in Italy were retrospectively identified. Results: 25 CAPs treated with the BAD technique were included. The most frequently perforated artery was the left anterior descending artery (32%) and spring‐coil wires with a hydrophilic coating were the most common culprit wires (68%). Mean sealing time was 46.9 ± 60.1 min, with no significant differences between CTO‐PCIs and non‐CTO PCIs ( p  = .921). Acute successful sealing of the CAP was achieved in 96% of the cases. Immediate cardiac tamponade occurred in 28% of patients, four during CTO PCI and three during non‐CTO PCI ( p  = .55). Two patients required pericardiocentesis during hospitalization, one patient developed acute kidney injury, and one patient underwent cardiac surgery due to severe mitral regurgitation. At 1‐year follow‐up no significant differences were observed between groups in terms of POCE (25 vs 25%, p  = .628) and its individual components. Conclusion: The BAD technique proved to be effective for the management of CAP, showing high successful sealing rates. Rates of in‐hospital events and at 1‐year follow‐up did not significantly differ between patients suffering CAP during CTO revascularization or during non‐CTO PCI.